2020
DOI: 10.1002/adem.202001169
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Aramid–Ceramic Aerogel Composite for Harsh Environment

Abstract: Nature-based plant fibers with thermal insulation performance have been widely used in wearable textiles such as cloth, gloves, shoes, etc. [1-4] To enhance the thermal insulation of textiles, synthetic fibers with novel structures such as hollow and ultrafine fibers have been developed. [5] Hollow fibers show a higher thermal resistance compared with solid ones while ultrafine fibers perform better than macrofibers. [4,5] However, the fiber textiles usually have a relatively low thermal insulation property in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 32 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…e prepared nanocomposites had a low thermal conductivity of 0.026 W/ mK, which is very promising for their use in thermal insulation applications. In another study, An et al [132] prepared ceramic aerogel-aramid fiber textile composite by in situ crosslinking reaction, and it was found that the composite had an excellent thermal insulation conductivity (as low as 0.034 W/mK) with high compressive strength (1.1 MPa).…”
Section: Incorporation Of Textiles Into the Aerogelsmentioning
confidence: 99%
“…e prepared nanocomposites had a low thermal conductivity of 0.026 W/ mK, which is very promising for their use in thermal insulation applications. In another study, An et al [132] prepared ceramic aerogel-aramid fiber textile composite by in situ crosslinking reaction, and it was found that the composite had an excellent thermal insulation conductivity (as low as 0.034 W/mK) with high compressive strength (1.1 MPa).…”
Section: Incorporation Of Textiles Into the Aerogelsmentioning
confidence: 99%
“…[16] Blends of hollow silica particles into a polymer matrix to fabricate thermal insulation films can produce robust mechanical properties, [17,41,42] but the intrinsic high thermal conductivity and low melting point of polymers constrain the potential of this class of materials. Recently, some technologies have been developed to reinforce aerogel particles with fibers (polymer fiber or fiberglass), such as electrospinning, [43] hot pressing, [44] and 3D printing, [45] which can produce both excellent thermal insulation and mechanical properties. For example, incorporation of hollow silica nanoshells into a matrix of polymer fibers by electrospinning can yield flexible insulation composite membranes with low thermal conductivities of 0.0236 W m -1 K -1 [46] and 0.016 W m -1 K -1 .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Yue et al fabricated a laminated fibrous membrane with high solar absorptivity (up to 90%) and infrared reflectance (70%) which improves skin surface temperature by 8.5 °C compared with polyester cloth. Another strategy of thermal management is to reduce the heat convection of wearable materials via controlling air molecule collisions inside the fabric . Aerogel materials have excellent thermal insulation properties due to the pore size of aerogel material being much smaller than the mean free path of the air molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy of thermal management is to reduce the heat convection of wearable materials via controlling air molecule collisions inside the fabric. 21 Aerogel materials have excellent thermal insulation properties due to the pore size of aerogel material being much smaller than the mean free path of the air molecules. 22 Following this strategy, Lyuet al 23 fabricated Kevlar nanofiber aerogel/phase-change materials with high thermal management capabilities and infrared emissivities; among them, Kevlar aerogel films have outstanding thermal insulation performances.…”
Section: Introductionmentioning
confidence: 99%